2019
DOI: 10.3390/ijms20215347
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1/PD-1 Axis in Glioblastoma Multiforme

Abstract: Glioblastoma (GBM) is the most popular primary central nervous system cancer and has an extremely expansive course. Aggressive tumor growth correlates with short median overall survival (OS) oscillating between 14 and 17 months. The survival rate of patients in a three-year follow up oscillates around 10%. The interaction of the proteins programmed death-1 (PD-1) and programmed cell death ligand (PD-L1) creates an immunoregulatory axis promoting invasion of glioblastoma multiforme cells in the brain tissue. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 130 publications
(136 reference statements)
3
121
0
2
Order By: Relevance
“…T cells recognize PD-1L and bind it with an adequate PD-1 receptor. The intracellular domain of the receptor consists of an (ITSM) tyrosine-based switch motif that activates an inhibitory cascade [118][119][120][121][122][123][124]. Downsignaling promotes tyrosine phosphatase 2/Zeta-chain-associated protein kinase 7 (SHP-2/Zap 70) interplay, resulting in dephosphorylation and a significant decrease in lymphocytic cytotoxicity and proliferation.…”
Section: Immune Checkpoints Vs Tlr-4mentioning
confidence: 99%
“…T cells recognize PD-1L and bind it with an adequate PD-1 receptor. The intracellular domain of the receptor consists of an (ITSM) tyrosine-based switch motif that activates an inhibitory cascade [118][119][120][121][122][123][124]. Downsignaling promotes tyrosine phosphatase 2/Zeta-chain-associated protein kinase 7 (SHP-2/Zap 70) interplay, resulting in dephosphorylation and a significant decrease in lymphocytic cytotoxicity and proliferation.…”
Section: Immune Checkpoints Vs Tlr-4mentioning
confidence: 99%
“…LGG is the main subtype of gliomas, which characterized with lower aggressiveness and well differentiation than GBM counterpart. A growing number of studies focus on the interplay between glioma and immunity, but most research attach great attentions to the GBM [24][25][26]. LGG seems to be ignored from the field of cancer immunotherapy due to its better prognosis than GBM.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of GBM immunology, proteins programmed death-1 (PD-1) and programmed cell death ligand (PD-L1) also play an important role. It is recognized that the disturbances in the expression of these particles increase the aggression and invasiveness of GBM cells in the brain tissue [142]. In their work, Cha et al, showed that metformin could also affect this link in the cancer process.…”
Section: Metformin and Immune Microenvironment Of Gliomamentioning
confidence: 99%